Professional development of teachers on the basis of a digital educational platform: Challenges to the expert community - Sklyarova, Tatyana V.; Egorov, Ilya V.; Naumova, Diana V. (Saratov State University, 2023)
The relevance of the research lies in the fact that teachers often fail to cope with the tasks of digital communication and their own learning via digital platform, and therefore, digital means become a kind of a communication barrier for them, instead of being a unifying bond. The research objective is to summarize the experience of psychological and pedagogical interaction with the participants of the professional development program based on a digital educational platform in order to identify psychological and pedagogical defi ciencies of working teachers, who are enrolled in the professional development program, and the challenges faced by the experts of the training program. The study hypothesizes that the teacher-training professional development program, organized on the basis of a digital educational platform, will allow us to identify specifi c challenges to the expert community caused by the practice of exclusively distant interaction, on the one hand, and on the other hand, it will help to identify professional defi ciencies of working teachers and to overcome them. Participants: 53 teachers working in diff erent regions of the Russian Federation aged from 21 to 70 years old with work experience from 1 to 40 years. Methods (tools): the questionnaire for fi xing the psychological and pedagogical problems of the interviewees and the signifi cance of the professional activity (by I. V. Egorov, D. V. Naumova, T. V. Sklyarova, L. B. Schneider), the expert method (included observation and expert assessments) to determine the manifestation of professional competencies of teachers. Results. The research results helped to fi nd out that under the conditions of online learning, teachers demonstrate commitment to the position of a passive participant/listener, rather than an active co-author of the process. It is shown that adult education (of teachers, in particular) becomes a challenge to the expert community: the established mental patterns, individual and habitual models of obtaining knowledge determine the internal resistance and distrust to digital learning tools. It is revealed that the key shortage of the students is insuffi cient digital communication. Conclusions: to overcome teacher defi ciencies the authors propose the construction of an individual educational route for professional development and the use of gamifi cation techniques in digital learning. Practical signifi cance: the results obtained will allow to adjust the professional development programs that are conducted via the digital platform